EXTRALINGUISTIC FACTORS IN CONVERSATIONAL SPEECH AND ITS APPLICATION IN SPEECH - Majidova, Zarnigor Mamajonovna (International Journal of Psychosocial Rehabilitation, 2020)
the information transmitted is formed on the basis of certain rules of language (intralinguistics) means that it meets the requirements of the text. Of information the interaction of the communicants in the transmission from the addressee to the addressee relations (extralinguistics) will be of great importance. In discourse, a person engages in their natural speech and non-verbal communication with his creative thinking and the creation of a certain situation, which was unique temperament, with activity in the communicative act, from the beginning of emotional processes acquires individuality with forgiveness. This is what creates the discourse, its diversity indicates that the main linguistic subject providing is the person will give.